Assessment on factors affecting logistics performance in battery industry in Guangxi, China - Ying, Tang (2013)
The main objective of this research is to examine the factors influencing logistics performance on battery industry in Guangxi China. The research investigates on six factors that affect the logistics performance such as inventory, facilities & warehouses, transportation, purchasing & sourcing, information & communication technology management. It also involves the factors affecting the general organizational performance. Data were collected from 10 selected battery companies in logistics department through questionnaire among the managers. Correlation analysis is used to examine the relationship between the six factors and logistics performance. The results on the mentioned factors indicated they were positively correlated with logistics performance in battery industries. The result suggests that transportation is the most important factors influencing logistics performance for the industry